2021
DOI: 10.1186/s13287-021-02532-1
|View full text |Cite
|
Sign up to set email alerts
|

A novel RIP1/RIP3 dual inhibitor promoted OPC survival and myelination in a rat neonatal white matter injury model with hOPC graft

Abstract: Background The dual inhibitors of receptor interacting protein kinase-1 and -3 (RIP1 and RIP3) play an important role in cell death processes and inflammatory responses. White matter injury (WMI), a leading cause of neurodevelopmental disabilities in preterm infants, which is characterized by extensive myelination disturbances and demyelination. Neuroinflammation, leads to the loss and differentiation-inhibition of oligodendrocyte precursor cells (OPCs), represents a major barrier to myelin rep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…The development of the brain white matter in P2‐5 neonatal rats is similar to that in human preterm infants with a gestational age of 23–32 weeks. Several studies have used a P3 neonatal rat WMI model, so we chose P3 rats 28,29,40,41 . Furthermore, in our study, we only selected male rats because other studies indicated that male neonatal rats had more severe brain damage than female rats under the same conditions 42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of the brain white matter in P2‐5 neonatal rats is similar to that in human preterm infants with a gestational age of 23–32 weeks. Several studies have used a P3 neonatal rat WMI model, so we chose P3 rats 28,29,40,41 . Furthermore, in our study, we only selected male rats because other studies indicated that male neonatal rats had more severe brain damage than female rats under the same conditions 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used a P3 neonatal rat WMI model, so we chose P3 rats. 28,29,40,41 Furthermore, in our study, we only selected male rats because other studies indicated that male neonatal rats had more severe brain damage than female rats under the same conditions. 42 Moreover, clinical studies have shown that the severity of brain injuries in male newborns is higher than that in female newborns, and the recovery ability of males is lower than that of females.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the aforementioned RIP1 type I, II, and III kinase inhibitors (Figure ), ,,, many compounds with new scaffolds or ones originating from natural products have also been reported in recent years. For example, a new class of dual-targeting inhibitors of RIP1 and RIP3 was designed and synthesized in Xia’s laboratory, among which compound ZJU-37 ( 67 ) (Figure A) showed the highest potency. A national invention patent (ZL201810826696.1, China), has been issued for the use of this compound to prevent and treat RIP1- and RIP3-related diseases.…”
Section: Rip1 Inhibitorsmentioning
confidence: 99%
“…Through its receptor 1 (TNFR1), TNF-α initiates three cell death pathways, i.e., 1) necroptosis, 2) RIP-1-dependent apoptosis and 3) RIP-1-independent apoptosis linked to the TNFR-associated death domain (TRADD) ( Cao and Mu, 2021 ). Interestingly, an inhibitor of RIP-1/RIP-3 prevents OPC apoptosis following a hypoxic stimulus in the neonatal rat brain ( Zhang et al, 2021 ). The neutralisation of TNF-α in the culture medium of LPS-activated microglia partially prevents OPC/Pre-OL death ( Pang et al, 2010 ; Taylor et al, 2010 ).…”
Section: Oligodendrocyte Lineage Response To Various Systemic Inflamm...mentioning
confidence: 99%